Forward secure proxy signature scheme - WANG Xiao-ming; CHEN Huo-yan; FU Fang-wei (Tongxin xuebao, 2005)
A forward secure proxy signature scheme was proposed combining the concept of forward security with proxy signature. This means even if an adversary has gotten the current proxy signers’ key. It could not forge proxy signature pertaining to the past, that is, previous generated proxy signatures remain still valid. Furthermore, the scheme can control the proxy signature time of the proxy singer.